The Pronunciation Errors Made by Students of Frist Grade of SMA Frater Makassar - Ryan Agung Kurnia; Baso Jabu; Munir Munir (Journal of Excellence in English Language Education, 2023)
This study aims to find out what sounds are wrongly spoken and the classification that causes pronunciation errors made by students. The method used in this research is descriptive qualitative with a sample of class X IPA 1 which consists of 20 students and the sample was selected by using the cluster random sampling technique. In obtaining the data, the researchers used a reading test and documentation (recording) as an instrument. The results found that pronunciation errors made by students amounted to 22 sound errors such as in sounds (e), (i), (i:), (l), (s), (k), (a), (p), ( ), (r), (h), (t), (ɡ) (z), (ʊ), (n), (ʌ), (f), (d), (c), (ͻ:) and (_). The classification of the causes of student pronunciation errors are 5 (five) such as mother tongue, phonological interference, avoidance, interlanguage transfer, and native language. So, it can be concluded that the pronunciation errors made by students are quite large, and the errors are caused by their first language so students often change the meaning. It is necessary to have extra practice for students in communicating and learning English so that there are no pronunciation errors so that in the future students can be better than before.